ANALISIS METAFORA KONSEPTUAL DALAM ARTIKEL POLITIK “MENATA ULANG KOALISI” - Mayang Pipit; Sjafty Nursitti NP Maili (Asosiasi dosen IDEBAHASA KEPRI, 2023)
The aim of this research was to describe the concept of metaphor which associated the source domain to the target domain in a political article as well as to see the scheme of metaphor that might appear in four related topics based on the text; coalition, government, politics and party. Research object was limited to metaphor in the level of single lexical form under qualitative approach and literature methodology by analyzing the written text. Based on the analysis, it was gained that the concept of metaphor leaded to the kind of structural metaphor which applied a certain structure to the target domain as followed “Coalition” and “Government” were “Body” and “Building”; “Policy” was “Building”, “Earthquake, Nobleman, Association, and Deposit”; “Party” was “Enemy, Friend, Tactic, and Stamp”.